Opportunities for Improvement of Dynamic Characteristics of Traveling-Wave Cathode-Ray Tubes and Their Signal Paths - Štaras, S.; Burokas, T. (Elektronika ir Elektrotechnika, 2005)
We analyze the influence of various factors on the dynamic characteristics of oscillographic traveling-wave cathode-ray tubes and their signal paths in order to find reserves for improving the dynamic characteristics, increasing operation speed and reducing linear distortions of signal form in the traveling-wave cathode-ray tubes. Delay dispersion, attenuation, change of characteristic impedance, change of the deflecting electric field, the transit time of electrons and other factors limit the width of the pass-band and the rise time of the transient response. The rise time of the transient response of a tube usually is less than the rise time of the signal path. The delay distortion has the most negative influence on the dynamic properties of the tubes and their signal paths. Avoiding “permissible” dispersion, characteristic impedance change versus frequency and deflecting electric field change versus frequency, we can shorten the transient response rise time and increase the width of the pass-band approximately 2 times for the signal path and about 2…2.4 times for the cathode-ray traveling-wave tube. Ill. 6, bibl. 13 (in Lithuanian, summaries in Lithuanian, English, Russian).